Comparison Between Bulgaria and Croatia in their Road Towards ERM II and The Banking Union of the EU - Simeonov, Kaloyan (Research Papers, 2021)
The last ERM II accession before July 2020 was in 2005. After the establishment of the Banking Union of the EU, starting from 2014, there was no enlargement of ERM II by EU Member State that is outside the Euro area. Therefore, the accession on 10 July 2020 of Bulgaria and Croatia to the ERM II on one hand and to the Banking Union on the other hand through the mechanism of the so-called close cooperation with the ECB represents a particular interest. The participation in these two mechanisms is a precondition for the accession to the Euro area and the adoption of the single currency. The comparison between the two countries shows that their path to the ERM II and the Banking Union is quite similar. However, there are also few peculiarities.